The Mediating Role of Emotion Regulation Within the Relationship Between Neuroticism and Misophonia: A Preliminary Investigation - Cassiello-Robbins, Clair; Anand, Deepika; McMahon, Kibby; Guetta, Rachel; Trumbull, Jacqueline; Kelley, Lisalynn; Rosenthal, M. Zachary (Frontiers in Psychiatry, 2020)
Misophonia is a newly described condition (Brout et al., 2018) characterized by heightened emotional reactivity (e.g., anger, anxiety, disgust) to common repetitive sounds (e.g., oral or nasal sounds made by others), accompanied by difficulties responding to these sounds (e.g., intolerance, avoidance, escape) and associated impairment in functioning. Although research indicates that problematic emotional responses are a key characteristic of misophonia, it is unknown whether individual differences in experiencing and regulating emotional responses influence severity of misophonia symptoms. Examination of individual differences in emotional functioning will help to guide treatment development for misophonia. Accordingly, the present study examined the associations among trait neuroticism, difficulties with emotion regulation, and symptoms of misophonia. For this study, a sample of 49 adults completed the Difficulties with Emotion Regulation Scale (Gratz, 2004), the Misophonia Questionnaire (Wu et al., 2014) and the neuroticism subscale of the NEO-Personality inventory (McCrae et al., 2005). Findings indicated that difficulties with emotion regulation and neuroticism were significantly positively correlated with symptoms of misophonia. Bootstrapped mediation analyses suggested that difficulties controlling impulsive behavior while experiencing intense negative emotions fully mediated the relationship between neuroticism and symptoms of misophonia. Results from this study suggest that neuroticism and difficulties with emotion regulation may be important risk factors and treatment targets for adults with misophonia, and difficulties controlling impulsive behavior when distressed may be an important individual difference accounting for the relationship between neuroticism and misophonia.